Engaging Students Interest in Learning Traditional Literature through Visual Novel - Mokhammad Sudrajat; Rizqi Claudia Wardani (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
The preservation of traditional literature in contemporary educational settings presents a significant challenge. These forms of entertainment have captured the interest of students, often at the expense of more classical literary forms. This study aims to maintain the existence of traditional literature by attracting students' interest in the learning process using visual novels as the medium, then we can rechange the students’ interest from other country products such as manga, webtoon, Korean drama back to traditional literature. As samples, students from the first semester of English Language Education program, University of Education of Muhammadiyah have been selected with a total of 19 students as respondents, there are 17 female students and 2 male students. The data collection technique used was a questionnaire with 20 statements, that using scale Likert from strongly disagree, disagree, agree, to strongly agree. The research method used is the Chi square method, in which this method is used to determine the correlation between students' interests and traditional literature in the form of visual novels. The research results obtained were that there was no relationship between student interest and traditional literature in the form of visual novels for English Education students. This is evidenced by the asymp value. Sign (2 sides) is greater than 0.05, so it can be concluded that H0 is accepted, and Ha is rejected. his outcome suggests that the intervention did not successfully alter students' preferences towards traditional literature. However, further analysis revealed an overall improvement in students' engagement and understanding of literary content when exposed to visual novels, as reflected in their feedback and academic performance. These findings highlight the potential of visual novels as a supplementary tool in literature education, even if they do not directly shift students' interests away from modern media.